Thyroid fine‐needle aspiration cytology: Performance data of neoplastic and malignant cases as identified from 1558 responses in the ASCP Non‐GYN Assessment program thyroid fine‐needle performance data. Issue 10 (9th June 2014) - Eilers, Stan G.; LaPolice, Paula; Mukunyadzi, Perkins; Kapur, Umesh; Wendel Spiczka, Amy; Shah, Ajay; Saleh, Husain; Adeniran, Adebowale; Nunez, Amberly; Balachandran, Indra; Clark, Jennifer J.; Lemon, Larry
Abstract : BACKGROUND: Fine‐needle aspiration of the thyroid is a common procedure, with an established role in reducing unnecessary thyroid surgery and identifying neoplasms and malignancies. METHODS: The study evaluated 1558 responses in the American Society for Clinical Pathology (ASCP) Non‐GYN Assessment program of aspirates of thyroid neoplasms and malignancies and placed them into the following groups: group A (target or correct interpretation), group B (incorrect interpretation as a benign thyroid nodule), group C (incorrect interpretation malignant aspirate as thyroid neoplasm), and group D (malignant diagnosis with incorrect interpretation). In clinical practice, responses in groups A, C, and D would lead to surgical excision, whereas responses in group B would not. RESULTS: Of a total of 1558 responses, 78.5% of the responses were in group A, 8.5% in group B, 3.75% in group C, and 9.25% in group D. By individual diagnosis, the group rates were 86.5%, 0%, 11%, and 2.5% for anaplastic thyroid carcinoma; 83%, 5.5%, 4.25%, and 7.25% for papillary thyroid carcinoma; 79%, 7%, 6%, and 8% for medullary thyroid carcinoma; 83.5% 6.75%, 0%, and 9.75% for Hürthle cell neoplasm; and 61%, 22%, 0%, and 17% for follicular neoplasm in groups A, B, C, and D respectively. CONCLUSIONS: Fine‐needle aspiration was effective in diagnosing thyroid neoplasms and malignancies and in separating thyroid nodules into surgical and nonsurgical categories. Data from a large group of cytology professionals showed good performance; however, there is room for improvement, especially in making specific diagnoses. In particular, follicular neoplasm and follicular variant of papillary thyroid carcinoma were challenging diagnoses for participants. Cancer (Cancer Cytopathol) 2014;122:745–750. © 2014 The Authors. Cancer Cytopathology published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : Data from 1558 responses in the American Society for Clinical Pathology Non‐GYN Assessment program for thyroid fine‐needle aspirates from thyroid neoplasms and malignancies were evaluated for the correct diagnostic interpretation as well as classifying the incorrect responses into treatment‐based groups (nonsurgical benign thyroid nodule, thyroid neoplasm, or malignancy). Participants generally performed well, except for the entities of follicular neoplasm and follicular variant of papillary carcinoma, which were challenging diagnoses to program participants.